2017
DOI: 10.1037/xhp0000361
|View full text |Cite
|
Sign up to set email alerts
|

Self-relevance prioritizes access to visual awareness.

Abstract: As we are cognizant of only a fraction of the available visual inputs at any given time, how is information selected for access to consciousness? In particular, does the personal significance of stimuli influence perceptual selection? Given that self-relevant information is prioritized during various stages of processing, here we hypothesized that self-association may privilege access to awareness under continuous flash suppression (CFS). The results supported this prediction. Compared with geometric shapes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 33 publications
9
67
2
3
Order By: Relevance
“…Our finding of early self-discrimination is consistent with studies of Chinese subjects (Sui et al, 2009 , 2012c ; Chen et al, 2011 , 2015 ; Fan et al, 2011 , 2013 ; Yang et al, 2012 ; Zhang et al, 2013 ; Guan et al, 2014 ; Liu et al, 2016 ) and Western populations (Herbert et al, 2011a ; Sui et al, 2012c ; Tacikowski et al, 2014 ). Research suggests that automatic processing bias towards self might not reflect stimuli familiarity but could be related to perceptual salient processing with social self-relevance, termed the self-prioritization effect (Macrae et al, 2004 , 2017 ; Sui et al, 2012a , b , 2015 ; Humphreys and Sui, 2015 ; Schäfer et al, 2015 , 2016 ). The self could be a center to integrate different information types at various processing stages (Sui and Humphrey, 2015 ), and the self-modulation effect could happen automatically or intentionally (Humphreys and Sui, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of early self-discrimination is consistent with studies of Chinese subjects (Sui et al, 2009 , 2012c ; Chen et al, 2011 , 2015 ; Fan et al, 2011 , 2013 ; Yang et al, 2012 ; Zhang et al, 2013 ; Guan et al, 2014 ; Liu et al, 2016 ) and Western populations (Herbert et al, 2011a ; Sui et al, 2012c ; Tacikowski et al, 2014 ). Research suggests that automatic processing bias towards self might not reflect stimuli familiarity but could be related to perceptual salient processing with social self-relevance, termed the self-prioritization effect (Macrae et al, 2004 , 2017 ; Sui et al, 2012a , b , 2015 ; Humphreys and Sui, 2015 ; Schäfer et al, 2015 , 2016 ). The self could be a center to integrate different information types at various processing stages (Sui and Humphrey, 2015 ), and the self-modulation effect could happen automatically or intentionally (Humphreys and Sui, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the most important roles of self is to discriminate one’s own from non-self or other-related stimuli. The widely reported self-prioritization effect in perception and memory suggests a social discrimination function of self (Macrae et al, 2004 , 2017 ; Sui et al, 2012a , b , 2015 ; Schäfer et al, 2015 , 2016 ). The components of N1 (50–150 ms), P2 (about 150–250 ms), and P300 (about 300–500 ms) have shown the advantage effect for self-relevant stimuli (Zhao et al, 2009 , 2011 ; Fan et al, 2011 ; Yang et al, 2012 ; Chen et al, 2015 ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings differ from previous research that has frequently found that prior expectations bias the starting point of evidence accumulation, rather than nondecision time (Mulder et al, 2012;Dunovan et al, 2014;Wiech et al, 2014;White et al, 2016;Barbosa et al, 2017;White et al, 2018). There is evidence, however, that temporal expectations hasten non-decision time (Jepma et al, 2012), as do stimuli that are self-relevant (Macrae et al, 2017). Like the temporal expectation study (Jepma et al, 2012), we fixed the relative starting point to 0.5 because we were comparing correct and incorrect behavioural responses (Voss et al, 2015).…”
Section: Discussioncontrasting
confidence: 98%
“…To explore the processes underpinning task performance, computational modeling (i.e., drift diffusion model (DDM) analysis) will be used to explicate the specific pathway (or pathways) through which ownership influences decisionmaking (e.g., Golubickis et al 2017Golubickis et al , 2018Macrae et al 2017). In any task context, there are two distinct ways in which decisional processing can be biased.…”
Section: The Current Researchmentioning
confidence: 99%